PENGARUH PROMOSI KESEHATAN MENGGUNAKAN ZOOM MEETING TERHADAP TINGKAT PENGETAHUAN KADER MENGENAI IMUNISASI DASAR - Fildawaty Hutabarat; Suryani Suryani; Imelda Imelda (NHM PRESS, 2022)
Given the importance of the role of cadres in implementing posyandu activities, especially in providing complete basic immunization, it is necessary to make efforts or breakthroughs in increasing cadre knowledge about basic immunization. The type of pre-experimental research design is one group pretest-posttest to see the effect of health promotion using zoom meetings on the level of knowledge of cadres about basic immunization. This research will be conducted at the Puskesmas Kebun Kopi Jambi City in February-July 2022. In this study, respondents' knowledge was measured, then given training using a zoom meeting, then knowledge was measured again. The population of this study were all cadres in the working area of ​​the Kebun Kopi Health Center, as many as 15 cadres. The sample of this research is 15 people using total sampling technique. The instrument used in this research is filling out a questionnaire. Univariable test using frequency distribution and bivariable test using paired t test because the data distribution is normal. Based on the results of the study, before being given health promotion using a zoom meeting, the average knowledge of respondents was 8.60 with a minimum value of 4 and a maximum of 13 and after 8.11.53 with a minimum value of 9 and a maximum of 14. Statistically it was proven that there was a significant effect of health promotion using zoom meeting. on the level of knowledge of cadres regarding basic immunization in the working area of ​​the Jambi City Coffee Garden Health Center in 2022.It can be concluded that there is an effect of health promotion using zoom meeting on the level of knowledge of cadres about basic immunization.